THE CONTRIBUTION OF MATHEMATICS LEARNING METHOD THROUGH THE IMPROVISATION OF THE STUDENT DISCIPLINARY - Septian Dedy Nugroho; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The dressing of students disciplinary at IX grade of MTs Muhammadiyah 2 Kalibening Banjarnegara in the Academic Year of 2016/2017 and to know the contribution of the student in mathematics learning at grade IX of Islamic Junior High School (MTs) Muhammadiyah 2 Kalibening 2 Banjarnegara in the Academic Year of 2016/2017. The type of this research was qualitative by wing purpose sampling. The subject was collected from IX-A. The data was collected using observation and questionnaire. Content validation was used to analyze the instrument of the research. The research was analyzed by using the descriptive qualitative method. Barect on the result of the research, the researcher concludes that the method is learning on a tribute by improvising the students' learning discipline at IX grade of MTs Muhammadiyah 2 Kalibening Banjarnegara Academic Year of 2016/2017. It was shown by the achievement which students got before and after giving an action. The students' average score was 55, and into 57,67, re-teaching affected the low classroom. The middle classroom had an average score of about 60,33 at first and turned into 62,58 because it was given action. The improvement of student's disciplinary learning was contributed by conventional learning. Next, the full classroom about 70,2 before getting action. After giving an action, it increased by about 72. It can be concluded that the improvement of student's disciplinary learning was contributed by learning methods. The re-teaching learning method is contributive because it showed that the full classroom's improvement affects the bottom classroom.